Locating Preschool Literacy Practices: A Bio-Ecological Perspective on Irish Preschool Literacy Provision - Fiorentini, Clara Maria (Trinity College Dublin. School of Education. Discipline of Education, 2025)
The preschool years offer a unique window of time to support young children in developing emergent and early literacy skills prior to formal schooling. Ultimately, optimal emergent literacy support and early literacy learning experiences in preschool settings are dependent on educator knowledge and competence. While research on the educative nature of early childhood education demonstrates the crucial role of the early childhood educator in micro- and mesosystemic interactions, research demonstrating the role of the preschool educator as an early literacy educator, continues to be sparse. This research study explores early literacy practice and provision within the two final years of early childhood education in Ireland prior to beginning formal primary school education, more commonly known as the ECCE years. Reflecting on a systems-based approach to preschool literacy provision and the nature of meaningful interactions, this study acknowledges the unique and dynamic role of the preschool educator as an early literacy educator and the factors affecting the potential of their individual influence on children's early literacy learning experiences and development across the preschool years. Using a Mixed Methods Sequential Exploratory Design approach under a pragmatist methodology, this research explores the perspectives of preschool educators, managers and CPD providers on preschool literacy provision through two phases of data collection. Phase 1 offers quantitative data through a questionnaire of 194 preschool educators, consolidated and explored in greater depth through qualitative data generated through 20 semi-structured interviews with preschool educators (10), preschool managers (6), and preschool literacy CPD providers (4). This study offers an informative interrogation of existing priorities for preschool literacy provision in Ireland. The study confirms that appropriate recommendations and guidance for preschool literacy learning in Ireland are limited, leading to significant variety in preschool early literacy approaches and methods. Such uncertainties often result in a premature focus on overly formalised or 'schoolified' literacy practices in Irish preschool settings. Through a Bioecological lens, this study considers what currently informs existing early literacy practices in Irish preschools and unpacks a range of ongoing challenges associated with preschool literacy provision in terms of educator knowledge, pedagogical practices, resourcing, and broader sector-wide issues. The findings of this study offer valuable insights into patterns within existing priorities for preschool literacy practices, with particular attention to accommodations for, and value of, the read aloud as an intentional early literacy method and proximal process in the preschool years. Findings also offer insights into inconsistencies in the early literacy training experiences of preservice early childhood educators, the lack of practical supports across relevant frameworks and curricula, and an absence of suitable continuous professional learning opportunities for preschool educators. Bronfenbrenner's Bioecological Systems Theory emerges as a fundamental element of the study providing a valuable theoretical framework for studies of preschool literacy learning and research examining the educative nature of the preschool learning environment. Key recommendations for policy and practice in relation to preschool literacy provision and the quality of preservice educator literacy training are identified in the context of preschool and national domains.
APPROVED